Prioritizing Sustainability Performance through Importance Performance Map Analysis in State Enterprises - Agung Dinarjito; Sri Widiyastuti; Darmansyah Darmansyah; Suratno Suratno; Syahril Djadang (Penerbit Goodwood, 2026)
Purpose: This study evaluates the sustainability performance of State-Owned Enterprises (SOEs) (SOEs) using Importance-Performance Matrix Analysis (IPMA), focusing on Green Intellectual Capital (GIC), Green Organizational Identity (GOI), and Green Innovation (GI). Methodology: The study employs Structural Equation Modeling-Partial Least Squares (SEM-PLS) with data collected from 227 managerial respondents across Indonesian SOEs. SmartPLS version 4 was used for data analysis. Results: The results show that GIC and GI significantly enhance sustainable performance. IPMA indicates that several Green Human Capital (GHC) and Green Structural Capital (GSC) indicators such as environmental competencies, training, leadership support, Research and Development (R&D) investment, and environmental management systems are highly important but underperforming. Meanwhile, GI demonstrates both high importance and strong performance in supporting sustainability outcomes. Conclusions: GIC and GI are the main drivers of SOEs sustainability performance. Although the GOI has a relatively weaker direct effect, it remains important for supporting sustainability-oriented practices. The findings suggest that SOEs should prioritize environmental training, employee competency development, R&D investment, and environmental governance to improve sustainability performance. Limitations: This study is limited by its cross-sectional design, reliance on self-reported questionnaire data, and focus on Indonesian SOEs, which may limit the generalizability of its findings. Contributions: This study contributes to the sustainability literature by integrating SEM-PLS and IPMA to identify the importance of sustainability drivers and priority areas for managerial improvement. The findings provide practical guidance for SOEs managers and policymakers to allocate resources to enhance sustainability performance.